PENGARUH KURIKULUM 2013 TERHADAP PENINGKATAN PEMBELAJARAN BAHASA ARAB PADA SISWA KELAS VII MTS PONDOK PESANTREN PUTRI UMMUL MUKMININ AISYIYAH WILAYAH SULAWESI SELATAN - Syah Witri Islamiah (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the application of the 2013 curriculum to learning Arabic and the effect of the 2013 curriculum on learning Arabic in class VII students of Islamic Boarding School Ummul Mukminin Aisyiah.The research method used is a quantitative method. Data collection is done by means of observation, tests and documentation. This population as many as 115 students while the sample class VII A as an experimental class with a total of 38 students and class VII C as a control class with a total of 38 students students.The results of the study can be seen that the application of the 2013 curriculum has been applied regularly and well only needs to be developed later through inferential statistical testing namely by using the t test. Then obtained ttable = 1.67. So tcount ttable (8.53 1.67). so H0 is rejected and H1 is accepted. Thus it can be concluded that reading skills by memorizing students in the presence of a pretest compared to students without a pretest is very influential in improving Arabic language learning.Keywords: 2013 curriculum, improvement of learning